The structure of atomic gas around the supernova remnant 3C 400.2 - Giacani, E. B. (1998)
The interaction of the SNR 3C 400.2 with the interstellar medium is investigated on the basis of the HI observations using the Synthesis Radio Telescope at the Dominion Radio Astrophysical Observatory (DRAO). These new data show the existence of a dense atomic cloud associated with 3C 400.2 in the velocity range +14 to +42 km s -1 , and high velocity clouds probably accelerated by the supernova blast wave at  km s -1 and +69 km s -1 . We propose that the complex remnant 3C 400.2 is the result of a supernova explosion in a region of the interstellar medium containing a density discontinuity. A breakout phenomenon may explain the observed morphology in the different spectral regimes.